REKONSTRUKSI KONSEP JILBAB PERSPEKTIF MUHAMMAD SYAHRUR (Telaah terhadap Q.S. an-Nur [24]: 31 dan al-Ahzab [33]: 59) - AZKIYA KHIKMATIAR (Jurnal Ilmiah Ilmu Ushuluddin, 2019)
Syahrur is a contemporary Muslim scholar who offers an innovative theory in Islamic law that is the theory of limits (hudud) which is divided into two namely the maximum limit (hadd al-A'la) and the minimum limit (hadd al-Adna). This paper will answer about how Muhammad Syahrur interprets the veil in Q.S. an-Nur [24]: 31 and al-Ahzab [33]: 59 by using his boundary theory. The results of the study of the two verses are on the minimum limit (hadd al-Adna) generally accepted is to cover the upper region (al-juyub al-ulwiyah), namely the area of the breast, under the armpit, and close the lower intimate area (al -juyub as-sufliyyah). While the maximum limit (hadd al-A'la) generally applicable is the part included in the category of al-juyūb, whether al-juyub al-'ulwiyyah or al-juyūb as-sufliyyah ie the whole body of women except the face and both palms.